Determining the Influence of KemTRACE Cr and/or Micro-Aid on Growth Performance and Carcass Composition of Pigs Housed in a Commercial Environment - J. T. Gebhardt; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; J. Loughmiller; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2016)
A study was conducted to determine the interactive effects of chromium propionate (KemTRACE Cr; Kemin Industries Inc., Des Moines, IA) and Micro-Aid (Yucca schidigera-based product; Distributors Processing Inc., Porterville, CA) on growth performance and carcass composition of finishing pigs housed in a commercial environment. There were a total of 1,188 pigs (PIC 337 × 1050; initial BW = 60.3 lb) with 27 pigs/ pen and 11 pens/treatment. Pigs were split by gender upon arrival at the facility, with 5 blocks of each gender and a final mixed sex gender block. Gender blocks were randomly allotted to groups of 4 pen locations within the barn. Diets were corn-soybean meal-dried distillers grains with solubles-based and were fed in 5 phases. All nutrients were formulated to meet or exceed NRC (2012) requirement estimates. Treatments were arranged as a 2 × 2 factorial with main effects of Cr (0 vs 200 ppb) or Micro-Aid (0 vs 62.5 ppm). There were no Cr × Micro-Aid interactions observed for growth or carcass measurements. Overall, ADG and F/G were not influenced by treatment. Adding Cr alone increased (P = 0.048) ADFI, and inclusion of Micro-Aid resulted in a marginally significant increase (P = 0.076) in ADFI. For carcass characteristics, HCW, loin depth, and percentage carcass yield were not influenced by treatment. Backfat depth tended to increase (P = 0.055) and lean percentage was decreased (P = 0.014) when Cr was added to diets. In summary, no synergistic effects were observed from feeding Cr and Micro-Aid in diets fed to finishing pigs housed in a commercial environment. Only marginal differences were observed from adding Cr or Micro-Aid with increased ADFI observed from feeding either. Finally, diets containing added Cr tended to be associated with carcasses having more backfat and less lean suggesting the increased ADFI was not utilized for increased muscle deposition.
Keywords: chromium propionate; Micro-Aid; pigs